Green multi-tier supply chain management: An enabler investigation. Issue 2 (March 2018) - Dou, Yijie; Zhu, Qinghua; Sarkis, Joseph
Abstract: Stakeholder pressure, from actors including regulators, consumers and non-governmental organizations, has made organizations more responsible for poor environmental performance of their direct and sub-suppliers. Thus, green multi-tier supplier management (GMSM) has become an emergent topic. Yet it is still unclear how to enable GMSM practices effectively, i.e. how to enable sub-suppliers' environmental performance improvement. To help address the gap in the literature, this paper aims to identify enablers for sub-suppliers' environmental performance improvement, and it further applies a Decision-Making Trial and Evaluation Laboratory (DEMATEL)-based case study method to evaluate inter-relationships among these enablers and improve the focal company's GMSM practices, by using action research (AR) method principles. The data analysis and discussion with a follow-up evaluation after two years provided insights for the successful implementation of GMSM. The results show that top managers' support from the organizations is a prominent and necessary foundational enabler. An interesting observation is that close proximity of supply chain members is regarded as a very prominent enabler. Evaluation and feedback on these enablers two years later found that the enabler mapping was beneficial, allowing them to address the most influential enablers, and thus the GMSM practices of the focal company has been highly improved. This paper concludes with directions for further research. Highlights: Enablers for green multi-tier supply chain management (GMSCM) are identified. Cause and effect relationships among the enablers are evaluated. Top management support is a prominent and necessary foundational enabler. Close proximity of supply chain members is an important enabler for GMSCM. Field study shows enabler mapping benefits GMSCM implementation two years later.